CATALYZED 0RGANOSOLV PULPING OF SUNFLOWER (HELIANTHUS ANNUS) STEMS BY LOWER ALIPHATIC ORGANIC ACIDS (Biological Sciences - PJSIR, 2002)
Sunflower (Helianthus annus)  stems were  subjected  to organosolv  delignification  with  acetic, formic  and  propionic  acids. It was found that, among lower aliphatic organic acids, only acetic acid sufficiently delignified  this  raw  material.  The kinetics of delignification process was also studied and it was established that optimum acetosol v delignification  was  achieved with 95% acetic acid, and 0.25% hydrochloric acid as catalyst in 90 min of fractionation time. Further data on measurement and classification of fiber dimensions of this raw material showed the absence oflong fibres and abundance of short fibres  in  the pulp.